Síntese enzimática do ester oleato de etila a partir de lipases fúngicas de Penicillium sumatrense produzidas por fermentação no estado sólido - Zanella, Rcardo Antonio (2020)
The main objective of this work was the enzymatic synthesis of ethyl oleate ester from fungal lipases, which was produced by the strain Penicillium sumatrense isolated from castor leaves (Ricinus communis L., Euphorbiaceae), and applying rice husks and Sunflower Seeds Bran (FSG) as substrates in Solid State Fermentation (FES). The dosage of the enzymatic activity was determined by the titrimetric method, using olive oil as a substrate. To maximize the production of lipases, experimental plans were carried out with different proportions of substrates and inductors (glycerol). A catalytic activity value of 29.3 Ugss-1 was obtained in the optimum conditions (55% humidity, 25% FSG, 27 ºC) in 96 h of fermentation. The fermented material (lipase) obtained from the agro-industrial residue of rice husks and sunflower seed bran, was used in the studies of the synthesis of ethyl oleate in n-heptane, modifying the variables of temperature, enzymatic activity and molar ratio (RM, acid: alcohol). To evaluate the ester yield, the Lowry & Tinsley spectrometric method was applied and the statistical analyzes were performed using the Statistica 7.0 software. The best experimental conditions for the enzymatic synthesis of ethyl oleate were obtained with the ground substrate, molar ratio 1:6 (acid/alcohol), temperature 37 ºC and enzymatic activity of 60 Ugss-1, reaching out 100% conversion to ester in 5 hours of reaction.